2017
DOI: 10.1007/s12687-017-0312-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Asian Indian and Pakistani views about cancer and participation in cancer genetics research: toward the development of a community genetics intervention

Abstract: Cancer is a leading cause of mortality among the three million Asian Indian/Pakistanis (AIPs) in the USA. AIPs have traditionally been underrepresented in cancer-related research, although reasons remain largely unexplored. We sought to understand AIP's awareness and perceptions of cancer to improve their participation in risk assessment and cancer genetics research. Four focus groups, stratified by gender and birthplace (US-born vs. foreign-born), were held at an AIP cultural center. Discussions focused on kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…To our knowledge, research has yet to exhaustively explore public awareness of and attitudes toward genetic testing in Asia, such as India, Japan, Taiwan, China, and South Korea, and the few that have attempted to do so suggest a need to increase awareness [15][16][17][18]. Accordingly, through the present study, we sought (1) to examine awareness of genetic testing in Korea; (2) to assess difference in attitudes toward genetic testing among the general public, cancer patients, and health-care professionals; and (3) to suggest ways in which to improve and utilize knowledge of genetic testing for better patient care.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, research has yet to exhaustively explore public awareness of and attitudes toward genetic testing in Asia, such as India, Japan, Taiwan, China, and South Korea, and the few that have attempted to do so suggest a need to increase awareness [15][16][17][18]. Accordingly, through the present study, we sought (1) to examine awareness of genetic testing in Korea; (2) to assess difference in attitudes toward genetic testing among the general public, cancer patients, and health-care professionals; and (3) to suggest ways in which to improve and utilize knowledge of genetic testing for better patient care.…”
Section: Introductionmentioning
confidence: 99%
“…Moderated discussions with members of the AI population have revealed that individuals were unaware of family disease history and that they could benefit from genetic testing to assess risk. Reasons for hindrance to cancer risk discussions among AIs in our prior work included not wanting to cause stress to family members, fear of damage to family status in society with impact on marriage prospects, and cancer-related stigma (Leader et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In one of the first US-based studies, our team conducted 4 focus groups to explore knowledge, attitudes, and beliefs about cancer risk and prevention among the AI population in the greater Philadelphia area (Leader et al 2017). Results from the focus groups showed that (1) historically, more emphasis was placed on the treatment rather than the prevention of cancer, (2) cancer is highly stigmatized and family privacy and community standing greatly limit discussions of family and personal cancer history, (3) fatalism and karma reduced interest in seeking genetic evaluation for personal cancer risk, and (4) concern regarding access to health care services and financial difficulties hinders cancer screening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural barriers were not assessed in this study, but other studies have found that culture and language barriers are associated with a lack of confidence [18], the feeling of not belonging to the community [33], and low knowledge about health research [34] which may in turn, contribute to lower willingness to participate in research among Asian Americans. Advertising the study using culturally and linguistically relevant recruitment materials [35], increasing the number of Asian American CHWs and including Asian American researchers as part of the recruitment team [18] may help buffer the language and cultural barriers and increase Asian Americans' participation in research.…”
mentioning
confidence: 99%